Resective surgery for patients with frontal lobe diffuse low-grade glioma-related epilepsy: predictors of seizure outcomes. (December 2022) - Zhang, Kai; Liu, Dingyang; Yang, Zhuanyi; Li, Xuejun; Yang, Zhiquan; He, Xinghui
Background: Diffuse low-grade gliomas (DLGGs) are prone to invade the frontal lobes, with seizures being the most common symptom. However, limited attention has been paid to surgical outcomes and their predictors in patients with frontal DLGG-related epilepsy. Objective: This study aimed to analyze predictors of postoperative seizure outcomes in patients with frontal DLGG-related epilepsy. Design: This is a single-center retrospective study. Methods: This study retrospectively collected data of 115 patients with frontal DLGG-related epilepsy who underwent resective surgery between January 2014 and January 2021. Patients were categorized into favorable and unfavorable seizure outcome groups based on the International League Against Epilepsy (ILAE) classification. Univariate and multivariate analyses were used to identify potential predictors of seizure outcomes. Results: The mean follow-up was 4.11 ± 2.06 years, and 77.4% (89 of 115) of patients were seizure-free. Permanent neurological deficits were observed in 7.0% (8 of 115) of patients. Univariate and multivariate analyses revealed that total tumor removal [odds ratio (OR), 0.31; 95% confidence interval (CI), 0.12–0.82; p  = 0.018] and older age at seizure onset (OR, 0.96; 95% CI, 0.93–0.99; p  = 0.042) were independent predictors of favorable seizure outcomes. Conclusion: Surgical resection is an effective treatment for frontal DLGG-related epilepsy. Favorable seizure outcomes are more likely to be achieved in patients with complete tumor removal and those with older age at seizure onset.